Prevalence and risk factors for brucellosis in prolonged fever patients in post-conflict Northern Uganda - Muloki, Harriet N (Afr Health Sci, 2018)
BACKGROUND: Brucellosis is a disease with significant public and economic implications but strategies for controlling this disease remain problematic. OBJECTIVES: This study sought to determine the sero-prevalence of brucellosis in prolonged fever patients and to identify modifiable risk factors for the infection in humans in post conflict Northern Uganda. METHODS: The study employed a cross-sectional method among prolonged fever patients who had visited selected health facilities in the study districts in Northern Uganda. Sero-prevalence of brucellosis was calculated for i-ELISA IgG/IgM. A structured questionnaire was used to obtain data on possible risk factors for brucellosis. Associations between sero-prevalence and risk factors were measured using the Odds Ratio. RESULTS: Brucellosis was confirmed in 18.7% of the 251 patients that tested positive for the disease, with the rapid Brucella Plate Agglutination Test, and ages 10–84 years (median age 47+0.86). Sex (p = 0.001; OR 3.79; 95% CI 1.75 – 8.24), rearing livestock (p < 0.005; OR 8.44; 95% CI 2.84–25.03) and consumption of unpasteurised milk (p = 0.023; OR 2.57; 95% CI 1.14–5.80) were factors associated with brucellosis. CONCLUSION: Control of brucellosis in animals, training and sensitisation of the community on brucellosis is needed to stimulate action on human brucellosis control.